2021
DOI: 10.1038/s41598-021-87917-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and disease severity in an Iranian population of inpatients with COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) can present with a variety of symptoms. Severity of the disease may be associated with several factors. Here, we review clinical features of COVID-19 inpatients with different severities. This cross-sectional study was performed in Imam Reza hospital, Mashhad, Iran, during February–April 2020. COVID-19 patients with typical computed tomography (CT) patterns and/or positive reverse-transcriptase polymerase chain reaction (RT-PCR) were included. The patients were classified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
1
10
1
4
Order By: Relevance
“…A recent interventional study carried out in Southern Iraq by Al-Ibrahimi and Nihad 67 revealed associated with severe COVID-19 cases. These findings are in agreement with results of Nabavi et al72 study in Iran which revealed that COVID-19 symptoms with oxygen saturation and CT scan are helpful in prediction of the disease severity. Our study found a significant association between positive past medical history like HT and thyroid diseases and COVID-19 severity (p=0.002).…”
supporting
confidence: 93%
“…A recent interventional study carried out in Southern Iraq by Al-Ibrahimi and Nihad 67 revealed associated with severe COVID-19 cases. These findings are in agreement with results of Nabavi et al72 study in Iran which revealed that COVID-19 symptoms with oxygen saturation and CT scan are helpful in prediction of the disease severity. Our study found a significant association between positive past medical history like HT and thyroid diseases and COVID-19 severity (p=0.002).…”
supporting
confidence: 93%
“…After deleting duplicates, we identified 2463 studies from four databases and then screened articles by title and full text according to the study's objectives. Finally, 69 studies were included in the meta-analysis (Figure 1), of which 62 studies had assessed risk factors for death from COVID 2889 ); 13 studies determined risk factors for severity (( 41,50,5355,65,…”
Section: Resultsmentioning
confidence: 99%
“…Acute respiratory syndrome in COVID-19 is the main cause of hospitalization in the intensive care unit (ICU) and death ( 6 ). Cytokine storm is the main cause of organ dysfunction among these patients ( 7 ).…”
Section: Introductionmentioning
confidence: 99%